Bioorthogonal-targeted 1064 nm excitation theranostic nanoplatform for precise NIR-IIa fluorescence imaging guided efficient NIR-II photothermal therapy - Zhang, Wansu; Deng, Weixing; Zhang, Hua; Sun, Xiaoli; Huang, Ting; Wang, Wenjun; Sun, Pengfei; Fan, Quli; Huang, Wei (Biomaterials, 2020)
Application of 1064 nm activatable NIR-IIa fluorescence imaging (FI) and NIR-II photothermal therapy (PTT) results in high-resolution imaging and good deep-tissue therapy, respectively. Combining NIR-IIa FI with NIR-II PTT may allow precise diagnosis guided efficient treatment of deep-tissue tumors. However, designing a 1064 activatable theranostic nanoplatform using a single dye for both NIR-IIa FI and NIR-II PTT is a challenge. Herein, we synthesized squaraine-based semiconducting polymer nanoparticles (PSQPNs-DBCO) that were excited by a 1064 nm laser for precise NIR-IIa fluorescence imaging guided NIR-II PTT treatment. Combined with bioorthogonal labeling technology, the PSQPNs-DBCO largely accumulated in the tumor section, extremely enhancing signal-to-background ratio (SBR) of imaging and NIR-II PTT efficiency of tumor in live colorectal-bearing animals. [Display omitted]